PHENOMENON OF THREAT IN LINGUISTIC THEORY AND FORENSIC PRACTICE - A. Baranov (Теория и практика судебной экспертизы, 2014)
The paper argues for a need to take on board the basic principles of «natural language» communication, as a universal approach that helps to reveal the latent semantics of written text (including the intention of threat). The author di!erentiates between several types of threat as an act of speech (punishment threat, warning threat, and coersion threat), lists their key characteristics, and recommends that forensic linguistic inquiry should investigate the seven proposed aspects of a threat situation.